Estudio comparativo en derecho objetivo y derecho indígena en el caso de la niñez y adolescencia y las concepciones que sobre infancia tienen los pueblos indígenas de la parroquia Veintimilla del cantón Guaranda. - Baños Avilés, Paul (2013)
This thesis , for a law degree from the courts of the Republic of Ecuador , by Bolivar State University , takes an approach to customary law relating to children and adolescents. The research took place in the Bolívar province , canton Guaranda, area of high concentration of indigenous people of the Kichwa Nationality of Ecuador , people Guaranka . The research proposed overall objective to develop a comparative study , from the legal sciences, Law and Common Law Objective in relation to children and adolescents. Specifically, the objectives of the study are summarized in the following : a) identifying conceptions of childhood and adolescence are present in the Ecuadorian legal framework from the looks of objective law and customary law , b ) define the elements from customary law , shape the legislation on children and adolescents , and c ) develop training tools aimed at operators of indigenous justice as leaders, leaders and staff health and education. The research question underlying this study answers the following question : what is the conception of children and adolescents is present in the objective application of the law and common law ? Working hypotheses are summarized in the following : i ) The eyes of children and adolescents from the objective law applied differ from those that support the application of customary law ; ii ) The Common Law in areas with high concentration of indigenous population are more host that the application of objective law , and iii ) the application of justice from customary law has no materials that enable reflection and unification of criteria. Considered a qualitative research design . The sample was not randomly selected according to the objectives of the research related to available information arising from key people with high knowledge of customary law applied to children and adolescents . The analysis and processing of data Página | 8 considered the theoretical principles of descriptive statistics . Percentages, bar charts and summary tables of information were used. Additionally the data found by consulting experts in law, education and multiculturalism were validated . The main conclusion from the study establishes poor compatibility between the objective law and customary law applied to children and adolescents, there emerges the need to promote technical capabilities - juridical justice officials (leaders, leaders, elders , personal health and education ) of the Bolivar province , canton Guaranda for the application of customary law rules relating to children and adolescents with respect to criteria and generation of valid rights jurisprudence. Other conclusions are: normativizada information is required in relation to conceptions of childhood and adolescence from the common law , it is essential to identify unifying criteria relating to the administration of justice by operators of Customary Law in childhood and adolescence , the who combine research presents alternative visions of objective law and customary law on issues of adolescence and childhood. A basic recommendation that emerges from the thesis is generally methodologies and tools for the development of capabilities to operators of Justice from customary law that lead to the generation of a conceptual framework of how structured and applied indigenous justice in childhood and adolescence based a clear and structured criteria.